Scent from Jasminum grandiflorum flowers: Investigation of the change in linalool enantiomers at various developmental stages using chemical and molecular methods. (August 2017) - Pragadheesh, V.S.; Chanotiya, Chandan S.; Rastogi, Shubhra; Shasany, Ajit K.
Abstract: Jasminum species are among the most preferred fresh cut flowers in India since ancient times. The plant produces small and fragrant flowers, which are of great demand in the preparation of fragrant garlands and also in perfume industries. Floral volatile of Jasminum grandiflorum L. (Family: Oleaceae) was extracted using solid-phase microextraction and analyzed in enantioselective gas chromatography. Chemical classes of identified volatiles revealed the presence of terpenoids, phenylpropanoids, and fatty acid derivatives. Marker constituent of flower volatiles, linalool was selected for analytical characterization on ethyl- and acetyl-β-cyclodextrin stationary phase. ( R )-(˗)-Linalool was found as major enantiomer in volatiles of floral buds whereas ( S )-(+)-linalool predominated in the volatiles of matured flowers. Simultaneously, a quantitative real-time PCR was performed to find the gene expression of linalool synthase to investigate the mechanism of enantiomeric inversion. The emission pattern of ( R )-(˗)-linalool at different flower developmental stages was well correlated ( P = 0.01) with the gene expression of the cloned linalool synthase from J. grandiflorum . We observed that the successive change in ( R )- to ( S )-linalool ratio from bud to mature flower was mainly due to the enantio- specific transformation and temporal decline of ( R )-linalool producing gene in J. grandiflorum . This enantiomeric change also leads to the difference in flower aroma. Furthermore, this is probably the reason behind consumer's acceptance for jasmine buds rather than bloomed flowers in cut flower segments. Graphical abstract: Image 1 Highlights: Jasminum grandiflorum volatiles were studied on chiral phases by SPME technique. Emission of linalool at various anthesis stages were analyzed enantioselectively. ( R )-(˗)-Linalool was the predominant enantiomer in the buds but ( S )-(+)-linalool dominates in matured flower. Gene expression of linalool synthase was performed using quantitative real-time PCR. Emission of ( R )-(−)-linalool and linalool synthase gene expression was well correlated ( P = 0.01).